Preschool English teachers’ practices in early literacy instruction: A multiple case study / Nazila Seyed Hendi - Nazila , Seyed Hendi (2018)
The most important years of learning begin at birth. During these early years, a human being is capable of absorbing more information at a time than they will ever be able to gain. The practices preschool teachers implement in their classrooms are vital in children’s early literacy development. Preschool teachers are always expected to implement research-based literacy practices to make sure children are ready to learn when they enter school. This qualitative case study intended to address four non-native in-service preschool English teachers’ practices in early literacy instruction. These teachers were selected from two preschools in the northwest of Kuala Lumpur in Malaysia. Data collection involved field notes and videotaping of classroom practices along with interviews and documents from ten full English lesson observations in each classroom. Data analysis began with identifying teachers' practices. Teaching techniques the teachers used as they set about trying to implement these practices were then examined across a range of instructional events. The data record was also examined to see how these teachers promote social interaction in their classrooms. From these analyses, a case study of each teacher's English literacy practices was developed. A final step involved conducting a cross-case analysis. The major contributions of the study related to the vitality of the professional development and curriculum in early childhood education in providing support for teachers’ efforts as well as the importance of teacher education training programs in preparing preschool teachers to be able to explore the key elements of early English literacy and its context and consequently deliver appropriate instruction in classrooms. In other words, through proper training and support, preschool teachers can attain the proficiency in literacy instruction and thus be successful in boosting early literacy skills and motivation of young children. Besides, conducting this research has indicated that curriculum can be a useful tool and guide in helping teachers focus instruction on significant goals. However, curriculum is not helpful unless teachers understand it and know how to use and implement it in actual practices. They are required to comprehend how these practices can be implemented to enhance or build suitable and efficient literacy experiences for young children in their early years. It is hoped that the current study offers some valuable information and understanding about ways preschool teachers provide educational opportunities to young children and how they implement social interaction in their classrooms to help children develop early English literacy. It also intended to offer insights on how to train preschool teachers so that they become competent in early English literacy instruction.